Brain Metastases From Lung Adenocarcinoma May Preferentially Involve the Distal Middle Cerebral Artery Territory and Cerebellum - Kwon, Hyeokjin; Kim, Jun Won; Park, Mina; Kim, Jin Woo; Kim, Minseo; Suh, Sang Hyun; Chang, Yoon Soo; Ahn, Sung Jun; Lee, Jong-Min (Frontiers in Oncology, 2020)
Although whole-brain radiation therapy (WBRT) is the mainstay of treatment for brain metastases (BMs), the concept of saving eloquent cortical lesions has been promoted. If lung cancer BMs are spatially biased to certain regions, this approach can be more justified. Here, we evaluated whether lung cancer BMs show a preference for certain brain regions and that their distribution pattern might differ according to the histologic subtype of primary lung cancer. In this retrospective study, 562 BMs in 80 patients were analyzed (107 BMs from small cell carcinoma, 432 from adenocarcinoma, and 23 from squamous cell carcinoma). Kernel density estimation was performed to investigate whether the BM spatial patterns differ among lung cancer subtypes. Further, we explored more detailed sub-regions where BMs occur frequently in adenocarcinoma using one-way ANOVA. Lastly, we divided our cohort into those with fewer (≤10) and more (>10) BMs and evaluated if this biased pattern is maintained across limited and extensive stages. For small cell carcinoma, BMs were biased to the cerebellum, but this did not reach statistical significance. For adenocarcinoma, BMs were found more frequently near the distal middle cerebral artery (MCA) territory and cerebellum, compared with other arterial territories (p < 0.01). The precentral and postcentral gyri were the most significant sub-regions within the distal anterior cerebral artery (ACA) and MCA territories (p < 0.01). Crus I and Lobule VI were significant regions within the cerebellum (p < 0.01). Regardless of the number of BMs, the affinity to the distal MCA territory and cerebellum was maintained. The present data confirm that BMs from lung adenocarcinoma may preferentially involve the distal MCA territory and cerebellum.